Singapore : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper examines the behavior of savings and investment from an Asian and Singaporean perspective. It builds and estimates two econometric models that relate savings and investment to a range of macroeconomic and structural variables. The paper examines the relationship between labor market developments and private consumption behavior, and notes that employment uncertainty did have a significant negative impact on consumption and raised precautionary savings. It also examines quantitative, industry-level measures of the intensity of domestic competition in the manufacturing and services sectors during the past two decades in Singapore.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet